DEVELOPMENT OF ONTOLOGICAL DECISION MAKING SYSTEM OF THE NEGOTIATION PROCESS ON COOPERATION PRODUCTION IN AIRCRAFT - Yuriy Vorobyov; Igor Shostak; Svetlana Kryvova; Alexander Zubanyov (Сучасний стан наукових досліджень та технологій в промисловості)
Subject matter: means of information support for the negotiation process on the organization of cooperative production of aircraft. Goal: an outline of the process of developing effective means of information support for negotiations on cooperative production, which will provide financial savings, firstly, by reducing the negotiation time, and secondly, is reducing the likelihood of making irrational decisions that can lead to additional costs during project implementation. Tasks: Increase the efficiency of the negotiation process on the organization of cooperative production by creating a problem-oriented methodological basis, and on this basis - software tools for the development, deployment and operation of the appropriate decision support system. Methods: system analysis and set theory, for the formal presentation of relevant information about the subject area "Negotiations on cooperative aircraft production"; ontological engineering, in particular the IDEF5 standard, as well as elements of expert systems technology, for building an ontological decision support system. Results: an aggregate of methodological tools for the synthesis of ontological decision support systems was developed during negotiations on the organization of cooperative production of aircraft, a scenario example of organizing an ontological dialogue in the environment of an ontological decision support system for defining an aircraft model as an object of cooperative production was given. Conclusions: the need to supplement the mathematical support of traditional negotiation support systems with special methodological means is shown to increase the efficiency of information support for the negotiation process on organizing cooperative production in aircraft construction; it is substantiated that for the program implementation of the system of information support for negotiations on the organization, it is advisable to use the ontological approach; the architecture of the intellectual core of the ontological decision support system for organizing the negotiation process for organizing the cooperative production of aircraft in the form of a hierarchy of frames, with the organization of knowledge-based inference by means of attached procedures is proposed; a scenario example of the formation of a decision on the choice of an aircraft model for the organization of cooperative production in the environment of an ontological decision support system is given.